Bubble formation in co-fed gas–liquid flows in a rotor-stator spinning disc reactor. (July 2016) - de Beer, M.M.; Keurentjes, J.T.F.; Schouten, J.C.; van der Schaaf, J.
Highlights: Co-fed gas–liquid flows in a rotor-stator spinning disc reactor are studied. High speed imaging and spectral analysis of pressure drop signals is employed. Two bubble formation mechanisms observed: gas overpressure and turbulent vortices. Maximum homogeneously dispersed gas flow linearly proportional to turbulence intensity. Pressure signature of gas–liquid flows enables continuous monitoring of the process. Abstract: The gas–liquid flow in a rotor-stator spinning disc reactor, with co-feeding of gas and liquid, is studied for high gas volumetric throughflow rates and high gas/liquid volumetric flow ratios. High speed imaging and spectral analysis of pressure drop signals are employed to analyse the flow. Two mechanisms of bubble formation are observed, one due to gas overpressure leading to large irregular bubbles, and one due to liquid turbulent vortices leading to small, well-defined bubbles. The two mechanisms lead to three distinct gas dispersion regimes, distinguished by their characteristic oscillations in pressure drop. At low rotational Reynolds numbers ( Reω < 0.4 · 10 6 ), in the gas spillover regime, the gas is dispersed as large bubbles only. Above this critical Reω, small bubbles are sheared off as well, thus forming a heterogeneous dispersion. At sufficiently high Reω, depending on the gas flow rate, the gas is homogeneously dispersed as small bubbles. The maximum gas flow that can be dispersed as small bubbles is linearly proportional to the local energy dissipation rate. The understanding of the bubble formation mechanisms and pressure signature allows prediction and detection of the prevailing hydrodynamic regime in scaled up spinning disc reactors and for different reaction fluids.